2002
DOI: 10.1086/342283
|View full text |Cite
|
Sign up to set email alerts
|

Star Formation in the [ITAL]Infrared Space Observatory[/ITAL] Atlas of Bright Spiral Galaxies

Abstract: We investigate star formation along the Hubble sequence using the Infrared Space Observatory Atlas of Bright Spiral Galaxies. Using mid-infrared and far-infrared flux densities normalized by K-band flux densities as indicators of recent star formation, we find several trends. First, star formation activity is stronger in late-type (Sc-Scd) spirals than in early-type (Sa-Sab) spirals. This trend is seen both in nuclear and disk activity. These results confirm several previous optical studies of star formation a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…Using the empirical relations of Bell (2003) to convert the radio luminosity into star formation rate, we find ∼1 M ⊙ yr −1 in each case. The radio luminosity is thus consistent with being due to star formation typical for the S0-Sa/b morphology of the host galaxies (Bendo et al 2002).…”
Section: Multi-wavelength Data and Spectral Energy Distributionssupporting
confidence: 72%
“…Using the empirical relations of Bell (2003) to convert the radio luminosity into star formation rate, we find ∼1 M ⊙ yr −1 in each case. The radio luminosity is thus consistent with being due to star formation typical for the S0-Sa/b morphology of the host galaxies (Bendo et al 2002).…”
Section: Multi-wavelength Data and Spectral Energy Distributionssupporting
confidence: 72%
“…3 there is evidence of a weak correlation between h 850 / R 25 and morphological type. Using Infrared Space Observatory ( ISO ) observations of bright spiral galaxies (Bendo et al 2002), Bendo et al (2003) showed that star formation, as measured by mid‐infrared emission, is indeed more centrally concentrated in early‐type galaxies.…”
Section: Discussionmentioning
confidence: 99%
“…The mean SFR ratio for the late-types is 0.85 ± 0.08, implying that we miss ∼ 10−20% of the star formation by assuming that the emission-line gas follows an identical profile to the continuum emission. Star formation that is extended or that occurs preferentially in the outer regions of late type galaxies probably explains this result (e.g., Bendo et al 2002).…”
Section: Star Formation Ratementioning
confidence: 99%